2011
DOI: 10.4103/0972-124x.85676
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of unusual gingival enlargement post radiotherapy

Abstract: Oral changes following radiotherapy are not uncommon. Oral mucositis, alteration in salivary gland function, radiation caries, and gingival changes have all been reported following radiotherapy and chemotherapy. The gingival changes seen after radiotherapy may be unusual and often cause diagnostic dilemma. Metastasis to the gingiva has also to be ruled out in these cases. A 30-year-old female patient presented with enlargement of the gingiva of 6 months’ duration and lower lip swelling of 7 months’ duration. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, an unusual enlargement of the gingiva several months after the end of RT was mentioned in the literature, whereas the multiplication of gramnegative bacilli is cited as a possible mechanism for its occurrence. 5 A change in the oral microflora and an increase in the level of endotoxin released by gram-negative bacilli could play an important role in the development of inflammatory changes in the gingiva and lead to an altered tissue response and consequent gingival enlargement. Poor oral hygiene undoubtedly supports and accelerates the process of periodontium alteration; therefore, dentists must educate their patients undergoing RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an unusual enlargement of the gingiva several months after the end of RT was mentioned in the literature, whereas the multiplication of gramnegative bacilli is cited as a possible mechanism for its occurrence. 5 A change in the oral microflora and an increase in the level of endotoxin released by gram-negative bacilli could play an important role in the development of inflammatory changes in the gingiva and lead to an altered tissue response and consequent gingival enlargement. Poor oral hygiene undoubtedly supports and accelerates the process of periodontium alteration; therefore, dentists must educate their patients undergoing RT.…”
Section: Discussionmentioning
confidence: 99%
“…RT also causes inflammatory changes in the oral mucosa and gingiva, which can result in necrosis, atrophy, or unusual gingival enlargement. 5 Atrophy of the gingiva leads to recession and painful sensitivity in the exposed tooth root, whereas gingival enlargement causes food impaction and periodontitis. Based on the fact that ionizing radiation causes physical and chemical tissue damages, some authors suggested that applied RT causes dose-dependent alterations of the vascular flow in dental pulps, with possible but not necessarily permanent consequences: fibrosis and atrophy.…”
Section: Introductionmentioning
confidence: 99%